Blockchain technology in healthcare strengthening: The Nigerian case - Godsave Binlak Wazhi; Nengak Precious Danladi; Sesugh Daniel Terver; Stephen Ebuka Ukaobasi (BioSocial Health Journal)
Blockchain technology is a distributed ledger digital system that records all transactions on a network of interconnected systems in a way that is impossible to edit or hack. When blockchain is mentioned, thoughts of cryptocurrency pop into mind, but blockchain holds vast possibilities in other facets, such as big data analytics, research, the Internet of Things, healthcare, etc. Blockchain technology has many practical applications in the healthcare sector, including precision medicine and interoperability, supply chain management, authorization exchange of health information, security, and authorization, all of which are pivotal for effective health systems and quality health services. Significant hindrances have been inadequate infrastructure, lack of funding, computer literacy, and poor government policies. The challenge of establishing blockchain technology must be addressed. Exploring its architecture in the Estonian healthcare-based system, the possibility of its deployment in the Nigerian health sector is feasible with the right approach and government policies. This perspective paper discusses the potential benefits of blockchain in the health sector, the obstacles that impede the adoption of this technology, and the recommendations to overcome them. It aims to create awareness and close the significant gap between this idea and its implementation in our healthcare system. This will ultimately improve patient outcomes and strengthen our healthcare planning and management system.